Why Didn't They Get It? An Investigation into the Pedagogic Practices of a Vocational Curriculum - de Jager, Rae (School of Education, 2023)
There is a new player in the educational landscape in South Africa: private higher education institutions (PHEIs). These institutions often represent fourth generation professions and provide curriculum that are vocational in nature with an outward-looking approach. It is often the purpose of these curricula to prepare students for the world of work by providing them with the necessary skills and experience to be employable on completion of their studies. This study interrogates the pedagogic practices in a Live Sound, vocational course offered by Cape Audio College, a private provider of higher education in South Africa. Students are immersed in an authentic learning experience and the curriculum is centred around an assessment where students stage a Live Sound event that takes place in a real-world context. This study specifically examines the enabling and constraining factors that facilitate students to make the transition from learners to knowers. Furthermore, the study focuses on why, despite the student centred, authentic learning approach of the curriculum, students remained ambivalent about the curriculum as evidenced in their course evaluations. The study calls on Basil Bernstein's pedagogic device and in particular framing as the key analytical tool (Bernstein, 2000). Karen Ellery (2017) expands on Bernstein's theoretical ideas and these developments have been incorporated into the analysis in this study. This analysis takes a closer look at the regulative discourse as the social order of pedagogic discourse, in an attempt to reveal why, despite the strengthening of the framing of the instructional discourse as a result of a previous study, students were still ambivalent about the curriculum. Bernstein (2000) points out that the instructional discourse is embedded in the regulative discourse and that the regulative discourse is always dominant. The study reveals that without visible pedagogy students struggle to acquire the recognition and realisation rules to create relevant texts and successfully make the transition from learners to knowers. However, by its very nature, authentic learning implies a less visible pedagogy. Therefore, the lecturer, teacher and curriculum developer need to be aware of the inherent tension that is set up in such circumstances and will have to manage the learning space accordingly.